Keratoacanthoma centrifugum marginatum at an unusual site - Meghana M Phiske; Ganesh Avhad; H R Jerajani (Wolters Kluwer Medknow Publications, 2013)
Keratoacanthoma (KA) is a rapidly evolving tumor, composed of keratinizing squamous cells originating in pilosebaceous follicles and resolving spontaneously if left untreated. It is relatively uncommon in dark-skinned and occurs in middle aged individuals. Males are three times more affected than females. It presents as firm, rounded, flesh-colored or reddish papule; with a rapid growth phase followed by spontaneous healing over three months. Two types of KA exist i.e., solitary and multiple. There are three rare clinical variants of solitary KA, namely giant KA, keratoacanthoma centrifugum marginatum (KCM) and subungual KA. In KCM, lesions are large, reaching upto 20cms. There is peripheral extension with raised, rolled border and atrophy in the center. There is no tendency toward spontaneous involution. The most common locations are dorsa of hands and legs, lesions on scalp being rare. A rare case of KCM occurring on scalp which is an unusual site is reported.